2009
DOI: 10.1371/currents.rrn1052
|View full text |Cite
|
Sign up to set email alerts
|

Green tea catechins inhibit the endonuclease activity of influenza A virus RNA polymerase

Abstract: The influenza A RNA polymerase possesses endonuclease activity to digest the host mRNA. Thus this endonuclease domain can be a target of anti-influenza A virus drug. Here we report that green tea catechins inhibit this viral endonuclease activity and that their galloyl group is important for their function. Docking simulations revealed that catechins with galloyl group fit well into the active pocket of the endonuclease domain to enable stable binding. Our results provide useful data that make it possible to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 12 publications
1
92
1
Order By: Relevance
“…The documented anti-viral activities of EGCG include the inhibition of the influenza virus, 18) human immunodeficiency virus type 1 (HIV-1), 19,20) Epstein-Barr virus, 21,22) herpes simplex virus, 23) and hepatitis B virus. 24) In vitro, EGCG inhibited various viral enzymes, such as adenovirus protease adenain, 25) influenza A RNA polymerase, 26) and HIV-1 integrase. 27) EGCG bound to CD4 on T cells and prevented its interaction with HIV gp120.…”
Section: Discussionmentioning
confidence: 99%
“…The documented anti-viral activities of EGCG include the inhibition of the influenza virus, 18) human immunodeficiency virus type 1 (HIV-1), 19,20) Epstein-Barr virus, 21,22) herpes simplex virus, 23) and hepatitis B virus. 24) In vitro, EGCG inhibited various viral enzymes, such as adenovirus protease adenain, 25) influenza A RNA polymerase, 26) and HIV-1 integrase. 27) EGCG bound to CD4 on T cells and prevented its interaction with HIV gp120.…”
Section: Discussionmentioning
confidence: 99%
“…Kizuhara and co-workers have reported that green tea catechins inhibited this viral endonuclease activity and that their galloyl group was important for their function [93]. Docking simulations revealed that catechins with galloyl group fitted well into the active pocket of the endonuclease domain to enable stable binding.…”
Section: Catechinsmentioning
confidence: 99%
“…Much research has shown that plant extracts and natural products have a wide range of pharmacological activities, including anti-inflammatory, antibacterial, anticancer and antiviral [12]. For instance, polyphenols from green tea have the ability to inhibit influenza virus replication [19,20] and polyphenolic compounds derived from Phellinus baumii could inhibit influenza virus infection [10]. In recent years, the antiviral activity of some species of Paeonia has been explored.…”
Section: Uplc-q-tof-ms Analysismentioning
confidence: 99%